Diffusion imaging and transcranial magnetic stimulation assessment of transcallosal pathways in chronic stroke. Issue 10 (October 2015) - Mang, Cameron S.; Borich, Michael R.; Brodie, Sonia M.; Brown, Katlyn E.; Snow, Nicholas J.; Wadden, Katie P.; Boyd, Lara A.
Highlights Both transcallosal pathway structure and neurophysiologic function is altered by stroke. The impact of transcallosal pathway status on motor function and impairment post-stroke is not well understood. Diffusion imaging and transcranial magnetic stimulation assessments of transcallosal pathways can each provide unique information that is relevant to post-stroke motor impairment.